2020
DOI: 10.1155/2020/8823458
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dynamics in a Chemical Reaction under an Amplitude-Modulated Excitation: Hysteresis, Vibrational Resonance, Multistability, and Chaos

Abstract: This paper deals with the effects of an amplitude-modulated (AM) excitation on the nonlinear dynamics of reactions between four molecules. The computation of the fixed points of the autonomous nonlinear chemical system has been made in detail using the Cardan’s method. Hopf bifurcation has been also successfully checked. Routes to chaos have been investigated through bifurcations structures, Lyapunov exponent, phase portraits, and Poincaré section. The effects of the control force on chaotic motions have been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…To verify these analytical results, we have numerically studied the real and imaginary parts of the eigenvalues σ when c 1 varies from −1 to 11. By using the polynomial companion matrix and the standard eignvalue solver Lapack [46][47][48][49][50][51][52], the obtained results are shown in figure 2. From the analysis of this figure, we note that when −1 c 1 11, the zero eigenvalue still exists.…”
Section: Fixed Point Stability Analysismentioning
confidence: 99%
“…To verify these analytical results, we have numerically studied the real and imaginary parts of the eigenvalues σ when c 1 varies from −1 to 11. By using the polynomial companion matrix and the standard eignvalue solver Lapack [46][47][48][49][50][51][52], the obtained results are shown in figure 2. From the analysis of this figure, we note that when −1 c 1 11, the zero eigenvalue still exists.…”
Section: Fixed Point Stability Analysismentioning
confidence: 99%
“…where p � ω 2 0 (F 1 α 1 − η)/(ηc) and q � ω 2 0 (F 1 α 0 − F 0 η)/ (ηc). e roots of equation ( 9) can be derived as [46,62]…”
Section: Equilibrium Stability and Its Evolutionsmentioning
confidence: 99%
“…)/2. According to Cardan discriminant [46,62], when Δ ≻ 0, one positive real equilibrium point is obtained from (11), since the equilibrium point cannot be a complex number. us, the system possesses in this case, one Hopf bifurcation point (HBP).…”
Section: Equilibrium Stability and Its Evolutionsmentioning
confidence: 99%
“…In order to validate the analytical predictions, we have simulated numerically the set of Eqs. ( 25) and (26) to see the effects of the control parameters on the fractality of the basin of attraction. To this end, the obtained results are presented in Fig.…”
Section: Active Control 51 Effects Of the Control On The Horseshoe Chaosmentioning
confidence: 99%
“…It belongs to a category of nonlinear chemical reactions well developed in the scientific literature. We made this choice because it has already been demonstrated that a modified Van der Pol-Duffing oscillator can be used to model the nonlinear chemical oscillations like BZ reactions [21][22][23][24][25][26]. Since the control of regular and irregular motions is an interesting issue in several areas [27], the dynamical behavior of a forced generalized Rayleigh oscillator, which constitutes a new model for describing the nonlinear chemical oscillations, may be investigated.…”
Section: Introductionmentioning
confidence: 99%